Rola prawa karnego w systemie totalnej teokracji państwa muzułmańskiego - Limburska, Alicja (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
The aim of the study is to answer the question whether the way the system of criminal responsibility is shaped in classical Sharia law influences the characteristics of Islam understood as a political system seen as a total theocracy. The article presents the basic assumptions of the criminal law in Islam, focusing on the categories of crimes distinguished by traditional Muslim jurisprudence. The perceived features of Koranic criminal law regulation are juxtaposed with the attributes of criminal law of non-democratic systems, which leads to the conclusion that in the sphere of criminal law, there are many elements the two systems have in common. The individual’s position and the degree of protecting their rights resulting from the criminal law of Islam seem to make it impossible for a system based on classical Islamic law to meet the requirements of a modern democratic state.
Keywords: islam; prawo karne; totalitaryzm; teokracja